A Pengaruh Program Kemitraan dan Endorsement terhadap Efektivitas Digital Marketing: Peran Mediasi Kesadaran Merek pada UMKM - Joenarni, Elly; Ridha, Mokhammad; Kridaningsih, Anna; Sholeh, Rachmad (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to identify factors influencing the effectiveness of digital marketing among SMEs in Mojokerto City through a quantitative survey. The sample consists of 95 randomly selected SME owners from a population of 1,625, using the Henry King nomograph with a 5% margin of error. Data were collected through a questionnaire measuring partnership programs, celebrity endorsements, brand awareness, and digital marketing effectiveness, analyzed using PLS-SEM and Ordinary Least Squares (OLS). Key findings indicate that both partnership programs and celebrity endorsements significantly impact digital marketing effectiveness through increased brand awareness. Partnership programs directly enhance brand awareness, while endorsements positively influence brand perception. The analysis shows that brand awareness serves as a significant mediator linking partnership programs and endorsements with digital marketing effectiveness, supporting Keller’s (2001) brand equity theory, which positions brand awareness as the foundation of consumer-brand relationships. In a digital context, strategic collaborations with influencers and well-planned partnerships emerge as critical for effective marketing, suggesting the importance of a holistic strategy that integrates partnerships and endorsements. This research demonstrates that integrating partnership programs and endorsements into digital marketing strategies effectively enhances brand awareness, which, in turn, improves campaign effectiveness. Looking ahead, SMEs need to strategically engage with partners and celebrities aligned with their brand values to achieve maximum impact. The practical implications highlight the importance of establishing brand awareness as an initial step in digital strategies, while socially and ethically, this study emphasizes the necessity of transparency and authenticity in selecting endorsers and partners to avoid consumer manipulation.